FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KETIDAK LENGKAPAN IMUNISASI DASAR PADA BAYI - Sarimin, Dorce Sisfiani; Yulidar, Elfina; Yulianita, Yulianita; Yuningsih, Risna; Shahab, Fatinah (Ensiklopedia of Journal, 2024)
Based on the initial survey, it is known that Puskesmas Lima Puluh has the lowest percentage of complete basic immunization achievements in Pekanbaru City at 26% of the national target of 100%. The purpose of the study was to determine the factors associated with incomplete basic immunization in infants in the working area of Puskesmas Limapuluh Pekanbaru City.This type of research is quantitative with a cross-sectional study design. The population in the study were all mothers who had babies aged 9-11 months in the working area of Puskesmas Lima Puluh with a total sample of 49 people. The sampling technique used simple random sampling. The results showed that there was a variable relationship between knowledge (p value 0.030), KIPI (p value 0.028), and family support (p value 0.004) to the incompleteness of basic immunization in infants in the Lima Puluh City Puskesmas working area. The conclusion of the study is that the variables associated with incomplete basic immunization in infants in the working area of Puskesmas Lima Pulu Pekanbaru City include knowledge, KIPI, and family support. It is recommended for Puskesmas Lima Puluh to increase the role of cadres in conducting basic immunization socialization and proactively reminding mothers regarding immunization schedules.Keywords: Basic Immunization, KIPI, Knowledge